2015
DOI: 10.1182/blood-2014-05-576157
|View full text |Cite
|
Sign up to set email alerts
|

The hidden genomic landscape of acute myeloid leukemia: subclonal structure revealed by undetected mutations

Abstract: The analyses carried out using 2 different bioinformatics pipelines (SomaticSniper and MuTect) on the same set of genomic data from 133 acute myeloid leukemia (AML) patients, sequenced inside the Cancer Genome Atlas project, gave discrepant results. We subsequently tested these 2 variant-calling pipelines on 20 leukemia samples from our series (19 primary AMLs and 1 secondary AML). By validating many of the predicted somatic variants (variant allele frequencies ranging from 100% to 5%), we observed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…The average number of mutations was higher in our data set in comparison with the TCGA cohort because we integrated 2 variant calling tools for single-nucleotide variant detection; this is a recently suggested strategy for improving cancer genome analysis. 34 We observed a significant age-related increase in the mutation number specifically in A-AML. This observation rules out (or at least highly reduces) the role of age as a potential confounding factor in the study and suggests that genomic instability increases with age in A-AML.…”
Section: Discussionmentioning
confidence: 65%
“…The average number of mutations was higher in our data set in comparison with the TCGA cohort because we integrated 2 variant calling tools for single-nucleotide variant detection; this is a recently suggested strategy for improving cancer genome analysis. 34 We observed a significant age-related increase in the mutation number specifically in A-AML. This observation rules out (or at least highly reduces) the role of age as a potential confounding factor in the study and suggests that genomic instability increases with age in A-AML.…”
Section: Discussionmentioning
confidence: 65%
“…However, mutations in genes such as FLT3, KIT, and RAS were found at low VAF, in line with previous reports which found that mutations in the RAS-FLT3 pathway tend to be subclonal. 43,44 The high sensitivity of NGS compared with other molecular techniques is especially important in these type of mutations, because patients harboring them could benefit from targeted therapy. Mutation distribution in this cohort agrees with previous reports demonstrating patterns of co-occurrence and exclusion among genes.…”
Section: Discussionmentioning
confidence: 99%
“…COAD samples had the largest fraction of concordant calls, where 243 out of the total 376 samples (88%) had a higher shared call percentage than the median in both GDC and MC3. In contrast, LAML samples exhibited the worst concordance between the two groups, which may be due to this cohort having incomplete demultiplexing, and using Whole Genome Amplification (WGA) in library construction (Bodini et al, 2015). From our analysis, we found that 79% of all the public somatic mutation calls from two groups were concordant.…”
Section: Somatic Mutationsmentioning
confidence: 84%